The golden bough; a study in comparative religion Vol 2 - Frazer, James George (Macmillan and co., 1894)
The Golden Bough, though discredited by its evolutionary assumptions and unscientific method, remains a treasury of exotic customs that appeal to many readers and of ideas anthropologists continue to wrestle with. The abridged edition, still in print, is enough for the reader to sample Frazer’s attitude toward “the dull mind of the savage.”
free
Keywords: Mythology